NEGATIVE PRESSURE WOUND THERAPY (NPWT) FOR THE MANAGEMENT OF DIABETIC FOOT WOUND - Heris Santy, Wesiana (Unusa Press, 2013)
Complications often experienced by people with diabetes are complications in the feet ( 15 % ) called diabetic foot ( Akhtyo , 2009) . Where the injury to the leg if not treated properly will lead to infections and ultimately need to be amputated .The purpose of writing articles is to review and discuss the evidence-based literature bersadarkanpraktice of Negative Pressure Wound Therapy Effectiveness ( NPWT ) ) on the healing of diabetic foot ulcers.One technology that is used to prevent and avoid lower limb amputation is the technique of negative pressure or Negative Pressure Wound Therapy ( NPWT ) ) . This negative pressure technique has grown rapidly and now has been widely used in many countries , especially in Western European countries ( Germany ) and the United States . Negative pressure technique has the advantage that it is relatively cheaper cost than the use of hyperbaric oxygen . Results obtained by several studies that the use of NPWT may improve wound healing process through efforts to create a moist wound environment and decrease edema that becomes optimal wound healing , throw that out of the wound exudate so that the protease enzyme in the exudate also go wasted , this enzyme is known to interfere wound healing process . The other benefit is that it can stimulate cell growth by increasing angiogenesis physically , so that the growth of new cells will be maximal